A top-down approach for fabricating three-dimensional closed hollow nanostructures with permeable thin metal walls - Barrios, Carlos Angulo; Canalejas-Tejero, Víctor (Beilstein Journal of Nanotechnology, 2017)
We report on a top-down method for the controlled fabrication of three-dimensional (3D), closed, thin-shelled, hollow nanostructures (nanocages) on planar supports. The presented approach is based on conventional microelectronic fabrication processes and exploits the permeability of thin metal films to hollow-out polymer-filled metal nanocages through an oxygen-plasma process. The technique is used for fabricating arrays of cylindrical nanocages made of thin Al shells on silicon substrates. This hollow metal configuration features optical resonance as revealed by spectral reflectance measurements and numerical simulations. The fabricated nanocages were demonstrated as a refractometric sensor with a measured bulk sensitivity of 327 nm/refractive index unit (RIU). The pattern design flexibility and controllability offered by top-down nanofabrication techniques opens the door to the possibility of massive integration of these hollow 3D nano-objects on a chip for applications such as nanocontainers, nanoreactors, nanofluidics, nano-biosensors and photonic devices.
Keywords: nanocages; nanocontainers; nanofabrication; nanophotonics; nanoreactors; optical devices; plasmonics; top-down techniques